Non-Performing Loan and its Impact on Stock Price Index Through Return on Equity in the Banking Industry - Zakaria, Zakaria; Khotimah, Khusnul; Saling, Saling; Rasyid, Abdul (Innovation Business Management and Accounting Journal, 2023)
This research aims to examine and analyze the influence of non-performing loans on the stock price index through return on equity in the banking industry listed on the Indonesia Stock Exchange. The study employs secondary data from 30 banking industries obtained from ICMD (Indonesia Capital Market Directory) for the period 2016 to 2020, as well as data from the Central Bureau of Statistics, Bank Indonesia, Jakarta Stock Exchange website, and Bank Indonesia. The data is analyzed using path analysis with AMOS version 7 to test the data and analyze the hypotheses. The research findings indicate the following: 1) Non-performing loans have a significant negative influence on return on equity, meaning that lower non-performing loan values in an industry lead to higher profitability levels measured by return on equity; 2) Return on equity has a significant positive influence on the stock price index, explaining that higher profits for banks, as measured by return on equity, correspond to higher stock prices as measured by the stock price index; 3) Non-performing loans have a significant negative influence on the stock price index through return on equity. This suggests that investors are more responsive to changes in non-performing loans rather than waiting for financial performance information, as measured by return on equity, to assess stock price developments.